2015
DOI: 10.1016/j.chom.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics, Pediatric Dysbiosis, and Disease

Abstract: Antibiotics are by far the most common medications prescribed for children. Recent epidemiological data suggests an association between early antibiotic use and disease phenotypes in adulthood. Antibiotic use during infancy induces imbalances in gut microbiota, called dysbiosis. The gut microbiome’s responses to antibiotics and its potential link to disease development are especially complex to study in the changing infant gut. Here, we synthesize current knowledge linking antibiotics, dysbiosis, and disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
390
2
18

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(417 citation statements)
references
References 136 publications
7
390
2
18
Order By: Relevance
“…Decreased species richness in infancy has been associated with a number of host pathologies. 13,25,40,41 To identify factors that significantly contribute to species richness, Gibson et al developed a generalized linear mixed model with individual included as a random effect, leveraging available metadata including infant health (e.g. CRIB II (Clinical Risk Index for Babies) score, day of life, gestational age, birthweight, delivery mode, and presence of positive culture), medications (e.g., antibiotics, caffeine, and iron), and maternal health (e.g.…”
Section: Antibiotics Disrupt the Preterm Gut Microbiota Richness Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased species richness in infancy has been associated with a number of host pathologies. 13,25,40,41 To identify factors that significantly contribute to species richness, Gibson et al developed a generalized linear mixed model with individual included as a random effect, leveraging available metadata including infant health (e.g. CRIB II (Clinical Risk Index for Babies) score, day of life, gestational age, birthweight, delivery mode, and presence of positive culture), medications (e.g., antibiotics, caffeine, and iron), and maternal health (e.g.…”
Section: Antibiotics Disrupt the Preterm Gut Microbiota Richness Andmentioning
confidence: 99%
“…3,[6][7][8] Perturbation of the gut microbiota during this key developmental window can have lasting effects on host physiology and disease risk. [9][10][11][12][13][14] One of the most common perturbations during this period, antibiotic therapy, 13,15 can substantially alter the gut microbiota and infant physiology. 10,[16][17][18][19][20][21] Because preterm infants are at high risk for infection, antibiotics are the most commonly prescribed medications in neonatal intensive care units (NICUs) in the United States ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Besides short-term-efects, the dysbiosis produced by antibiotics administration in infants may produce long-term efects like the persistence of the risk of obesity development. It has been observed that 3 months after of antibiotics persists the microbiota disruption [120]. However, antibiotic administration to neonates has been linked to several critical clinical conditions in which modiication of the microbiota composition is thought to play a relevant role, in diseases such as necrotizing enterocolitis and sepsis [121,122].…”
Section: Antibiotic Exposure and Dysbiosis In Childrenmentioning
confidence: 99%
“…Нарушения становления микробиоты на ранних этапах онтогенеза могут способствовать в дальнейшем развитию атопии, бронхиальной астмы, ожирения. В настоящее время широко обсуждается роль микробиоты кишечника в пато-генезе аутизма [36].…”
unclassified